2021
DOI: 10.3389/fimmu.2020.612564
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Differentially Expressed Immune Biomarkers in Latent and Active Tuberculosis by Real-Time PCR

Abstract: Tuberculosis (TB) remains a major global threat and diagnosis of active TB ((ATB) both extra-pulmonary (EPTB), pulmonary (PTB)) and latent TB (LTBI) infection remains challenging, particularly in high-burden countries which still rely heavily on conventional methods. Although molecular diagnostic methods are available, e.g., Cepheid GeneXpert, they are not universally available in all high TB burden countries. There is intense focus on immune biomarkers for use in TB diagnosis, which could provide alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 149 publications
(244 reference statements)
0
33
0
Order By: Relevance
“…Although many advances have been achieved, especially in omics field (60-62), there were some practical limitations for their clinical application, including expensive laboratory facilities and sophisticated operating procedures. Meanwhile, immunodiagnostics has received considerable attention as an alternative for discrimination of MTB infection status in recent years (63)(64)(65)(66)(67)(68)(69)(70). Nevertheless, the identified biomarkers including proteins and cytokines in serum or plasma for diagnostic aim may not be specific for TB due to the influence brought by other immune related diseases such as infection and autoimmune diseases (71)(72)(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…Although many advances have been achieved, especially in omics field (60-62), there were some practical limitations for their clinical application, including expensive laboratory facilities and sophisticated operating procedures. Meanwhile, immunodiagnostics has received considerable attention as an alternative for discrimination of MTB infection status in recent years (63)(64)(65)(66)(67)(68)(69)(70). Nevertheless, the identified biomarkers including proteins and cytokines in serum or plasma for diagnostic aim may not be specific for TB due to the influence brought by other immune related diseases such as infection and autoimmune diseases (71)(72)(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of our marker panel for distinguishing ATB from HC in such cases was high (96.3%), however, its sensitivity (71.2%) falls short of that specified in the WHO’s optimal Target Product Profile (TPP) for non-sputum-based TB diagnosis tests (98%) 47 . Nonetheless, like other biomarker studies published that similarly did not reach these standards 9 , 48 , 49 , our study has useful reference value for those engaged in biomarker discovery. Further work on optimizing this panel will be necessary.…”
Section: Discussionmentioning
confidence: 48%
“…The NCF1 gene colocalizes with two pseudogenes (NCF1B and NCF1C), where NCF1C expression responded robustly to PMA induction during macrophage differentiation (Bakry et al, 2021;Brunson et al, 2010). A recent study from England and India indicated NCF1C can be an immune biomarker to differentiate active tuberculosis and latent tuberculosis (Perumal et al, 2020). Our study has shown that the expression of NCF1C was 3.4-fold higher among household healthy controls than that of leprosy patients (Table 2 and Figure 6).…”
Section: Discussionmentioning
confidence: 51%